Psychometric Properties of the Outcome Rating Scale: An Item Response Theory Analysis. (3rd April 2021) - Toland, Michael D.; Li, Caihong; Kodet, Jonathan; Reese, Robert J.
Abstract: We assessed the psychometric properties of the visual analog scale (VAS) form of the Outcome Rating Scale (ORS) using item response theory (IRT) with a sample of 2, 109 Canadian counseling clients. Findings indicate that the ORS was unidimensional and that the equal-interval assumption was not tenable for the VAS.